Implementation Challenges of Performance-Based Capitation in Indonesia: A Scoping Review - Purnamasari, Ayu Tyas; rizki, Rizki Fadila (Tadulako University, 2025)
Performance-Based Capitation (KBK) is a payment system implemented in Indonesia’s primary health care (PHC) to improve service quality through performance-based financing. Despite its potential, various challenges have limited its effectiveness. This study aimed to identify and synthesize evidence on the barriers to KBK implementation in Indonesia. A scoping review was conducted using studies published from 2019 to 2025 that meet the inclusion and exclusion criteria. Data from 14 included studies were extracted, charted, and thematically analyzed into five categories: human resources, systems and infrastructure, program management and governance, technical capacity, and patient participation and engagement. The study found that face interrelated challenges in implementing KBK, including shortages and unequal distribution of human resources, inadequate systems and infrastructure, weak governance, limited technical capacity, and low community participation. These factors collectively hinder the achievement of key performance indicators encompassing contact rate, the non-specialist referral ratio (RRNS), and the controlled condition of the Chronic Disease Management Program (RPPT), underscoring the need for comprehensive strategies that strengthen workforce capacity, infrastructure, governance, and community engagement.